A STUDY ON ONLINE SHOPPING BEHAVIOUR (International Journal of Food and Nutritional Sciences, 2022)
On-line shopping is a recent phenomenon in the field of E-Business and is definitely going to be the future of shopping in the world. Most of the companies are running their on-line portals to sell their products/services on-line. Though online shopping is very common outside India, its growth in Indian Market, which is a large and strategic consumer market, is still not in line with the global market. The potential growth of on-line shopping has triggered the idea of conducting a study on on-line shopping in India. Recent research has shown an interest in investigating consumer motivations that affect the online shopping behavior. It is yet to understand what factors influence online shopping decision process.